2021
DOI: 10.1302/2633-1462.25.bjo-2020-0185.r1
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage revision for the infected total knee arthroplasty

Abstract: Aims Periprosthetic joint infection (PJI) is a devastating complication following total knee arthroplasty (TKA). Two-stage revision has traditionally been considered the gold standard of treatment for established infection, but increasing evidence is emerging in support of one-stage exchange for selected patients. The objective of this study was to determine the outcomes of single-stage revision TKA for PJI, with mid-term follow-up. Methods A total of 84 patients, with a mean age of 68 years (36 to 92), underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…As other studies have shown [29,30], patient selection for single-stage revisions remains critical. Polymicrobial infections are a major factor.…”
Section: Discussionmentioning
confidence: 99%
“…As other studies have shown [29,30], patient selection for single-stage revisions remains critical. Polymicrobial infections are a major factor.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding duplicates, 343 studies were included, and after evaluation of the title and abstract, 21 studies were analyzed. After assessing the eligibility of the full-text articles according to the inclusion and exclusion criteria and screening the bibliography of each article to find additional relevant publications, 18 clinical studies were selected and included in this systematic review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The PRISMA flowchart with the research strategy is shown in Fig.…”
Section: Search Strategy and Study Screeningmentioning
confidence: 99%
“…11 Single-stage revision has been used in the treatment of chronic PJIs to overcome technical difficulties in staged revision surgery, accelerate restoration of function, reduce morbidity, and decrease cost. [12][13][14] Zahar et al 15 recently reported the ten-year infection-free survival was 94% following single-stage septic hip exchange with an antibioticloaded bone cemented prosthesis due to PJI. We hypothesized that the combination of single-stage revision and intra-articular antibiotic infusion may be a feasible approach for PJIs after multiple failed prior surgeries for reinfection (PMFSR).…”
Section: System Statusmentioning
confidence: 99%